Maintenance costs of a pitch system of a wind turbine - Carvalho, Mariana (2013)
Although the wind turbines are nowadays the principal source of wind energy production, the technical information publicly known about these machines is still very scarce. Information related to failure modes, (un)availability and maintenannce costs of these systems remain confidential and only the manufacturer has knowledge about them. To be able to optimize the efficiency, to guarantee the security and to negotiate better warranty and maintenance contracts, it is necessary to know more information about the operation and maintenance and replacement costs of subsystems of a wind turbine. Thus, based on two years of operation, this paper exhaustively analyses an active power control system, of 21 identical wind turbines, installed in Portugal, reflecting on its operation, availability and maintenance and replacement costs, obtaining an estimate for the total maintenance cost of an active pitch control device.